On the protection of protected areas - Joppa, Lucas; Loarie, Scott R.; Pimm, Stuart L. (Proceedings of the National Academy of Sciences (USA), 2008)
Tropical moist forests contain the majority of terrestrial species. Human actions destroy between 1 and 2 million km2 of such forests per decade, with concomitant carbon release into the atmosphere. Within these forests, protected areas are the principle defense against forest loss and species extinctions. Four regions—the Amazon, Congo, South American Atlantic Coast, and West Africa—once constituted about half the world's tropical moist forest. We measure forest cover at progressively larger distances inside and outside of protected areas within these four regions, using datasets on protected areas and land-cover. We find important geographical differences. In the Amazon and Congo, protected areas are generally large and retain high levels of forest cover, as do their surroundings. These areas are protected de facto by being inaccessible and will likely remain protected if they continue to be so. Deciding whether they are also protected de jure—that is, whether effective laws also protect them—is statistically difficult, for there are few controls. In contrast, protected areas in the Atlantic Coast forest and West Africa show sharp boundaries in forest cover at their edges. This effective protection of forest cover is partially offset by their very small size: little area is deep inside protected area boundaries. Lands outside protected areas in the Atlantic Coast forest are unusually fragmented. Finally, we ask whether global databases on protected areas are biased toward highly protected areas and ignore “paper parks.” Analysis of a Brazilian database does not support this presumption.